Correlação entre comportamento tecnológico e propriedades petrográficas das rochas ornamentais silicáticas branco galaxy, ocre itabira e diamante negro - Pazeto, Abiliane de Andrade [UNESP]; Artur, Antonio Carlos [UNESP] (My University, 2015)
Brazil is globally known as one of the biggest producer and exporter of dimension stones, remaining since the 1990s among the six major producers. According to Abirochas estimates, the Brazilian production reached 10.5 million tons in 2013, comprising about 3.6 million tons for the foreign market and 6.9 million tons for the domestic one. The Brazilian exportation of dimension stones would have amounted US $ 1,302.11 million in 2013. It is noteworthy that the silicate rocks, involving granites and related rocks, represent almost 50% of the total Brazilian production. The use of these materials in civil construction has expanded every year, as a result of the increase in the national production levels and diversity of stones available on the market. However, despite these aspects, the technological properties of the rocky materials are poorly known, making their application empirical, thus, favoring the materials degradation. This paper evaluates the influence of the petrographic properties in the technological behavior of three granitic rocks of different mineralogical, textural and structural aspects. It has been established petrographic parameters for explaining and/or predicting the physical and mechanical behavior linked to the use of these rocks in building and masonry. In this context, the results showed a good correlation between the technological behavior and the petrographic properties intrinsic to each studied rock. They also allowed to determine the factors causing them, indicating that the three analyzed rocks are satisfactory, in terms of the physical-mechanical parameters, which favor their use as dimension stones.
Correlation between technological behavior and petrographic properties of branco galaxy, ocre itabira and diamante negro silicatic dimension stones
Keywords: Dimension stones; Granitic rocks; Petrographical properties; Technological characterization